Tectorial Membrane Material Properties in Tecta(Y)(1870C/+) Heterozygous Mice - Masaki, Kinuko (The Biophysical Society, 2010)
The solid component of the tectorial membrane (TM) is a porous matrix made up of the radial collagen fibers and the striated sheet matrix. The striated sheet matrix is believed to contribute to shear impedance in both the radial and longitudinal directions, but the molecular mechanisms involved have not been determined. A missense mutation in Tecta, a gene that encodes for the α-tectorin protein in the striated sheet matrix, causes a 60-dB threshold shift in mice with relatively little reduction in outer hair cell amplification. Here, we show that this threshold shift is coupled to changes in shear impedance, response to osmotic pressure, and concentration of fixed charge of the TM. In Tecta(Y)(1870C/+) mice, the tectorin content of the TM was reduced, as was the content of glycoconjugates reacting with the lectin wheat germ agglutinin. Charge measurements showed a decrease in fixed charge concentration from [Formula: see text] mmol/L in wild-types to [Formula: see text] mmol/L in Tecta(Y)(1870C/+) TMs. TMs from Tecta(Y)(1870C/+) mice showed little volume change in response to osmotic pressure compared to those of wild-type mice. The magnitude of both radial and longitudinal TM shear impedance was reduced by [Formula: see text] dB in Tecta(Y)(1870C/+) mice. However, the phase of shear impedance was unchanged. These changes are consistent with an increase in the porosity of the TM and a corresponding decrease of the solid fraction. Mechanisms by which these changes can affect the coupling between outer and inner hair cells are discussed.